Budaya Hidup Sehat Melalui Senam Kebugaran Jasmani Sehat Di Desa Telatan Kecamatan Semindang Alas Kabupaten Seluma - Pauzi, Zozan; Sumantri, Ajis (Universitas Dehasen Bengkulu, 2024)
This study aims to explore and analyse the implementation of healthy physical fitness exercises as part of a healthy living culture in Telatan Village, Semindang Alas Sub-district, Seluma District. The research method used was qualitative with a case study approach. Data were collected through in-depth interviews, participant observation, and document analysis related to the fitness programme. The results showed that healthy physical fitness exercises have become an integral part of the healthy living culture of the community in Telatan Village. Active participation in these activities not only improves physical health, but also strengthens social solidarity and community cohesion. Factors that support the implementation of fitness exercises include support from the local government, active participation of the community, and the availability of adequate facilities and amenities. However, challenges such as lack of financing and lack of understanding of the benefits of fitness exercises still need to be addressed. This study concludes the importance of promoting a culture of healthy living through healthy physical fitness exercises as an effective strategy to improve community welfare at the local level.